Neuropsychiatric symptoms in Alzheimer’s disease - J. Vegytė; R. Podėnė; E. Dlugauskas; A. Vaitkevičius (Neurologijos seminarai)
Alzheimer’s disease is one of the most common neurodegenerative diseases among older people that manifests as deterioration of cognitive functions, impaired daily activities, and progressive degeneration of cerebral cortex neurons. Even up to 90% of Alzheimer’s patients develop neuropsychiatric symptoms at different stages of the disease. In some cases, neuropsychiatric symptoms appear earlier than cognitive symptoms. Neuropsychiatric symptoms worsen everyday activities, quality of life, and ability to socialise of people with Alzheimer's disease, making the diagnosis and treatment of these symptoms increasingly important. Evaluation of both cognitive and neuropsychiatric symptoms together with differentiation from primary psychiatric disorders is crucial for the correct diagnosis of Alzheimer’s disease. Furthermore, neuropsychiatric symptoms can be considered as risk factors for the development of Alzheimer’s disease. Treatment is recommended with combined pharmacological and non-pharmacological measures. Despite the large number of studies, the pathogenesis of the neuropsychiatric symptoms has not been studied in depth, therefore the treatments provided are not always effective. It is recommended that neuropsychiatric symptoms should be treated through a combined approach using pharmacological and non-pharmacological measures.